BIOACTIVITY AND QUANTUM CHEMICAL CALCULATIONS OF A NEW COUMARINE DERIVATIVE AS A STRONG ANTIOXIDANT, ANTIMICROBIAL AND ANTI-CANCER SUBSTANCE - Koparir, Pelin (Soc Chemists Technologists Madeconia, 2023)
4-(((4-Ethyl-5-(thiophen-2-yl)-4H-1,2,4-triazol-3-yl)thio)methyl)-7-methyl-coumarin was synthesized, and its characterization was done with quantum chemical calculations and spectral techniques. The density functional method (B3LYP) with the 6-311G(d,p) basis set was used to calculate the molecular geometry, vibrational frequencies, and gauge, including atomic orbital (GIAO) H-1 and C-13-NMR chemical shift values of the title compound in the ground state. The theoretical vibrational frequencies and chemical shift values agree well with the experimental results. DFT calculations of the density of states (DOS) and frontier molecular orbitals of the title compound were carried out at the B3LYP/6-311G(d,p) level of theory. In the present study, biological activities and molecular docking studies of this triazole ring containing coumarin derivative compound were carried out. Interactions with important residues in active sites were detected in molecular docking studies. In addition, in vitro analysis has shown that anti microorganism activity is especially effective against bacterial organisms such as E. coli, S. aureus, B. cereus, and fungal organisms such as C. albicans, C. tropicalis. Also, the antioxidant capacity of the test compound was investigated by oxidative stress index (OSI) and radical scavenging power (DPPH.), and its antioxidant potential was found. In addition, it was determined by in vitro anticancer and SDS-PAGE analysis that the test compound does not cause a detrimental cytotoxic effect on healthy cell cultures such as HUVEC and has the potential for anticarcinogenic activity on MCF-7 and MKN-45 cancerous cell cultures.
Keywords: new coumarin; NMR; computational calculations docking; biological activity